Determination of components of the involvement process in innovative activity of teachers of higher education - Irina Fedorovna Filchenkova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article deals with the modeling of the process of engaging in innovative activity of high school teachers. The relevance of the problem is due to paradigmatic processes of modernization of Russian system of higher education. The author defines the involvement of innovation as a multidimensional, managed system of targeted processes. The article identifies the key components of the process of engaging in innovation processes innovation management in the University, the control factors of the environment of the University, management of personal and professional resources to overcome barriers for innovation activities and psycho-pedagogical support. Emphasizes the role of psychological and pedagogical support to overcome innovation barriers, systematizing external engagement processes. It is concluded that the management of the process of engaging in innovative activity of University teachers provides for the manifestation of innovative activity of teachers of the University.